Stiffness changes in internal rotation muscles of the shoulder and its influence on hemiplegic shoulder pain - Jia, Fan; Zhu, Xin-Rui; Kong, Ling-Yu; Fan, Jie-Cheng; Zhu, Zong-Jing; Lin, Li-Zhen; Zhang, Shu-Yun; Yuan, Xiang-Zhen (Frontiers in Neurology, 2023)
Background: Hemiplegic shoulder pain (HSP) is a common complication in patients with stroke. The pathogenesis of HSP is complex, and muscle hypertonia, especially the hypertonia of internal rotation muscles of shoulder, may be one of the important causes of shoulder pain. However, the relationship between muscle stiffness and HSP has not been well studied. The purpose of this study is to explore the correlations between the stiffness of internal rotation muscles and clinical symptoms in patients with HSP. Methods: Twenty HSP patients and 20 healthy controls were recruited for this study. The stiffness of internal rotation muscles was quantified using shear wave elastography, and the Young’s modulus (YM) of pectoralis major (PM), anterior deltoid (AD), teres major (TM), and latissimus dorsi (LD) were measured. Muscle hypertonia and pain intensity were evaluated using Modified Ashworth Scale (MAS) and Visual Analogue Scale (VAS), respectively. The mobility of the shoulder was evaluated using Neer score. The correlations between muscle stiffness and the clinical scales were analyzed. Results: The YM of internal rotation muscles on the paretic side was higher than that of the control group in the resting and passive stretching positions (P<0.05). The YM of internal rotation muscles on the paretic side during passive stretching was significantly higher than that at rest (P<0.05). The YM of PM, TM, and LD during passive stretching were correlated with MAS (P<0.05). In addition, the YM of TM during passive stretching was positively correlated with VAS and negatively correlated with Neer score (P<0.05). Conclusions: Increased stiffness of PM, TM, and LD were observed in patients with HSP. The stiffness of TM was associated with pain intensity of shoulder and shoulder mobility.